Self‐reported medication intake vs information from other data sources such as pharmacy records or medical records: Identification and description of existing publications, and comparison of agreement results for publications focusing on patients with cancer ‐ a systematic review. Issue 5 (5th March 2021) - Brüne, Manuela; Emmel, Carina; Meilands, Gisela; Andrich, Silke; Droste, Sigrid; Claessen, Heiner; Jülich, Fabian; Icks, Andrea
Abstract: Purpose: To identify and describe publications addressing the agreement between self‐reported medication and other data sources among adults and, in a subgroup of studies dealing with cancer patients, seek to identify parameters which are associated with agreement. Methods: A systematic review including a systematic search within five biomedical databases up to February 28, 2019 was conducted as per the PRISMA Statement. Studies and agreement results were described. For a subgroup of studies dealing with cancer, we searched for associations between agreement and patients' characteristics, study design, comparison data source, and self‐report modality. Results: The literature search retrieved 3392 publications. Included articles ( n = 120) show heterogeneous agreement. Eighteen publications focused on cancer populations, with relatively good agreement identified in those which analyzed hormone therapy, estrogen, and chemotherapy ( n = 11). Agreement was especially good for chemotherapy (proportion correct ≥93.6%, kappa ≥0.88). No distinct associations between agreement and age, education or marital status were identified in the results. There was little evaluation of associations between agreement and study design, self‐report modality and comparison data source, thus not allowing for any conclusions to be drawn. Conclusion: An overview of the evidence available from validation studies with a description of several characteristics is provided. Studies with experimental design which evaluate factors that might affect agreement between self‐report and other data sources are lacking.